Study Habits and university academic performance. The predictive power of on-line exams - Gamero-Burón, Carlos (2024)
Introduction: The adoption of efficient study habits is of great importance to achieve academic success in an increasingly demanding educational landscape. Objective: The relationship between study habits and academic performance among university students has been investigated. Method: The behavior of students regarding on-line tests has been taken as an indicator of study habits. From a stratified sampling, a random sample composed of 160 students enrolled in two first-year groups of the Degree in Business Administration and Management (ADE) at the University of Malaga has been obtained. Several quantitative analysis techniques are applied: descriptive and inferential analysis based on the estimation of non linear and linear regression models. Results: The results obtained suggest that students who delay the time to answer these tests obtain worse grades in these tests and in future exams, a lower probability of taking the final exam of the subject, and worse grades in this last exam. Discussion: The set of evidence obtained highlights the concern for the study habits adopted by higher education students. To a large extent, the achievement of the objective pursued by investment in education can be compromised if students do not adopt study strategies that allow them to achieve the goals and achievements established in the programs of the subjects studied. The adoption of inadequate learning strategies can short-circuit the line that links such investment with school performance.